Analisis Komprehensif Insiden Korupsi di Indonesia: Dampak pada Sektor Pendidikan dan Solusi Penanganannya - Frisnoiry, Suci; Waniza, Elva; Manullang, Juliana Maretty Citra; Andini, Putri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Corruption is a classic problem faced by the Indonesian people. This research aims to determine the condition of corruption in Indonesia and how to reduce corrupt actions based on analyses done by other research This research uses a literature review approach (library research). The data collection technique used in this research is documentation, collecting data from news websites. Corruption has a very detrimental negative impact on the economy and development of a country. Efforts to eradicate corruption must be done systematically and continuously to achieve optimal results for economic development and the welfare of society.